Mental Well-being Among Muslim Adolescents: Challenges and Strategies for Coping with Social Pressures - Imtihanatul Ma'isyatuts Tsalitsah; Akhsanul In’am; Abdul Haris; Muhammad Arfan Muammar (P3I UMSurabaya, 2025)
Mental well-being among Muslim adolescents is an important issue that increasingly demands attention due to the various challenges faced by the youth in a complex social context. This study aims to explore the challenges faced by Muslim adolescents in maintaining their mental well-being, as well as the strategies that can be implemented to cope with the social pressures they experience. Using a mixed-method approach, data were collected through surveys and in-depth interviews with Muslim adolescents from various regions in Indonesia. The results show that social pressures from the environment, such as expectations from family and society, as well as the influence of social media, significantly contribute to adolescents' mental health. Several strategies identified to improve mental well-being include social support, mental health education, and the development of effective coping skills to deal with stress and anxiety. This study underscores the importance of a community-based approach to support Muslim adolescents.